Universal screening for early detection of chronic autoimmune, metabolic and cardiovascular diseases in the general population using capillary blood (UNISCREEN): low-risk interventional, single-centre, pilot study protocol - Emanuele Bosi; Cristina Renzi; Vito Lampasona; Aurora Merolla; Rebecca De Lorenzo; Giulia Ferrannini; Francesca Ulivi; Elena Bazzigaluppi (BMJ Open)
Introduction Chronic autoimmune (type 1 diabetes and coeliac disease) and metabolic/cardiovascular (type 2 diabetes, dyslipidaemia, hypertension) diseases are highly prevalent across all age ranges representing a major public health burden. Universal screening for prediction/early identification of these conditions is a potential tool for reducing their impact on the general population. The aim of this study is to assess whether universal screening using capillary blood sampling is feasible at a population-based level.Methods and analysis This is a low-risk interventional, single-centre, pilot study for a population-based screening programme denominated UNISCREEN. Participants are volunteers aged 1–100 who reside in the town of Cantalupo (Milan, Italy) undergoing: (1) interview collecting demographics, anthropometrics and medical history; (2) capillary blood collection for measurement of type 1 diabetes and coeliac disease-specific autoantibodies and immediate measurement of glucose, glycated haemoglobin and lipid panel by point-of-care devices; (3) venous blood sampling to confirm autoantibody-positivity; (4) blood pressure measurement; (5) fulfilment of a feasibility and acceptability questionnaire. The outcomes are the assessment of feasibility and acceptability of capillary blood screening, the prevalence of presymptomatic type 1 diabetes and undiagnosed coeliac disease, distribution of glucose categories, lipid panel and estimate of cardiovascular risk in the study population. With approximately 3000 inhabitants, the screened population is expected to encompass at least half of its size, approaching nearly 1500 individuals.Ethics and dissemination This protocol and the informed consent forms have been reviewed and approved by the San Raffaele Hospital Ethics Committee (approval number: 131/INT/2022). Written informed consent is obtained from all study participants or their parents if aged <18. Results will be published in scientific journals and presented at meetings.Conclusions If proven feasible and acceptable, this universal screening model would pave the way for larger-scale programmes, providing an opportunity for the implementation of innovative public health programmes in the general population.Trial registration number NCT05841719.